Towards the issue of atmospheric air quality improvement strategy in Tomsk; Korus 2004; Vol. 1 - Panin V. E. Viktor Evgenyevich; Popov V.; Dashkovsky A.; Osipova N.; Dashkovskaia A. (2004, 2004)
The article discusses the principles of monitoring and atmospheric air quality management in the United Kingdom of Great Britain and Northern Ireland as one of the most successful country in this field. Under National Air Quality Strategy they developed national system of automated measurements of the concentrations of main atmospheric air pollutants. There are about 120 stations located mostly in the most urban areas and in the areas with rather background air pollution level. Local authorities create their own systems of monitoring, develop computer monitoring systems, that might replace the instrumental monitoring systems in the future. The key players in environmental protection movement in the UK are partnerships - associations of influential enterprises and municipal departments. Financial contributions of the members of the partnership in various environmental protection activities may succeed the environmental protection part of local budgets. On the basis of the comparative analysis of monitoring and atmospheric air quality management systems the rough draft of clean air strategy in Tomsk was developed. It covers the formation of a similar city partnership; development of the computer model of emissions' distribution in the atmosphere; development and implementation of environmental protection activities aiming at atmospheric air quality improvement in Tomsk